2017
DOI: 10.3389/fimmu.2016.00668
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Dimensionality Influences the Functional Response of Cytotoxic T Lymphocyte-Mediated Killing of Targets

Abstract: Cytotoxic T lymphocyte (CTL)-mediated killing of virus infections and tumors occurs over a wide range of conditions. The spatial environments in which CTLs encounter target cells vary from narrow vessels, to two-dimensional epithelial tissues, to densely populated 3-dimensional (3D) T cell areas within lymphoid tissues. How such spatial environments alter the functional response of CTL-mediated killing, i.e., how the killing efficiency depends on cell densities, is unclear. In this study, we perform cellular P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…We developed spatial simulations of CTLs killing in microwells, with the aim of generating noisy and undersampled artificial data representative of data generated by microscopy, data which can be used to test methods for recovery of parameters governing CTL hitting. To this end we employed the cellular Potts model (CPM) framework [ 34 ], a formalism we used previously to simulate T cell-target cell interactions [ 11 , 35 , 36 ]. The CPM is a lattice based model, with entities such as cells represented by assigning individual lattice sites a ‘spin’ value, to identify them as belonging to a specific entity.…”
Section: Methodsmentioning
confidence: 99%
“…We developed spatial simulations of CTLs killing in microwells, with the aim of generating noisy and undersampled artificial data representative of data generated by microscopy, data which can be used to test methods for recovery of parameters governing CTL hitting. To this end we employed the cellular Potts model (CPM) framework [ 34 ], a formalism we used previously to simulate T cell-target cell interactions [ 11 , 35 , 36 ]. The CPM is a lattice based model, with entities such as cells represented by assigning individual lattice sites a ‘spin’ value, to identify them as belonging to a specific entity.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely accepted in immunology that the physiological function of cytotoxic T cell (CTL) motility is to search for target cells, i.e., for virus-infected cells or cancer cells (15). Computational modeling studies have revealed that the search efficiency depends on the organization of the stromal environment of a tissue (16). In addition, the spatial behavior, for example, of HIV-infected target cells scanned for foreign antigens by CTLs strongly impacts the elimination efficiency of the infected targets (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our qualitative conclusions are also valid for 3D simulations for two reasons. First, the differences between 2D and 3D killing rates are quantitative rather than qualitative because encounter of targets by CTLs is more efficient in 3D spaces ( 19 , 20 ). Second, we find similar results in ODE models that consider well-mixed environments of arbitrary dimension.…”
Section: Discussionmentioning
confidence: 99%